Optimale Eigenfinanzierung der Personenunternehmen nach der Unternehmensteuerreform 2008/2009 - Stefan Homburg; Henriette Houben; Ralf Maiterth (Schmalenbachs Zeitschrift für betriebswirtschaftliche Forschung : Zfbf, 2008)
Effective from 2008, Germany's top marginal income tax rate rises from 42 to 45 per cent. However, sole proprietorships and partnerships can opt for a preferential tax rate of 28.25 per cent for retained profits ( 34a EStG). If they do so, profits are taxed again upon distribution. Using corporate finance tools, we analyse in detail whether or not the option is favourable. However, these wols do not suffice since the new tax regime is too complicated. Costs of capital cannot be calculated explicitly any more, but we derive exact implicit characterizations. Concrete numerical examples are also provided. – – Im Jahre 2008 steigt der Spitzensteuersatz der Einkommensteuer von 42 auf 45 Prozent. Einzel- und Mitunternehmer können jedoch für einen besonderen Steuersatz von 28,25 Prozent für einbehaltene Gewinne optieren. In diesem Fall werden die Gewinne bei späterer Entnahme nachversteuert. Der Artikel untersucht die Frage, ob die Option für den besonderen Steuersatz aus Unternehmersicht vorteilhaft ist.
Keywords: H25; 330; Income tax; Retained earnings; Einkommensteuer; Einbehaltene Gewinne; Thesaurierungsbegünstitung